2022
DOI: 10.3928/19404921-20220131-01
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Participate in Clinical Research Among Individuals With Cognitive Impairment

Abstract: This secondary analysis examined (1) factors associated with willingness to participate in clinical research for cognitive health among individuals with cognitive impairment and their care partners, and (2) concordance regarding such willingness between individuals with cognitive impairment and their care partners (dyads). Neuropsychological factors and willingness to participate in clinical research were collected using self-reported questionnaires. Participants' sociodemographic and clinical information was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…It provides insights into the views of “research‐engaged” individuals, mostly recruited through a dementia research registry, who reported positive attitudes toward research and were mostly people who had taken part in previous studies. Such characteristics are associated with willingness to participate in dementia research, 23 and research‐engaged people are a principal group to whom advance research planning initiatives should be directed. Our study contributes insights on the preferences such individuals would express in an ARD and how they would want their ARD used during potential future periods of decisional incapacity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It provides insights into the views of “research‐engaged” individuals, mostly recruited through a dementia research registry, who reported positive attitudes toward research and were mostly people who had taken part in previous studies. Such characteristics are associated with willingness to participate in dementia research, 23 and research‐engaged people are a principal group to whom advance research planning initiatives should be directed. Our study contributes insights on the preferences such individuals would express in an ARD and how they would want their ARD used during potential future periods of decisional incapacity.…”
Section: Discussionmentioning
confidence: 99%
“…People considering advance research planning may benefit from additional resources on drug studies—and other research that may be perceived as riskier—to inform their choices. This is important to ensure that people are aware of safety and ethical protections and also understand the differences between clinical care and research to avoid therapeutic misconception 42 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is possible that people with lower socialcognitive abilities may not be drawn to take part in research. Prior research has demonstrated that people with cognitive impairments are less willing to participate in clinical research and that these individuals tend to be difficult to recruit for study participation (Li et al, 2022). A larger number of participants recruited from different settings is needed to adequately assess social cognition in young people at FHR.…”
Section: Representativeness Of Study Samplementioning
confidence: 99%